2021
DOI: 10.1002/clc.23609
|View full text |Cite
|
Sign up to set email alerts
|

The use of minimal fluoroscopy for cardiac electrophysiology procedures: A meta‐analysis and review of the literature

Abstract: Background Conventional catheter ablation involves prolonged exposure to ionizing radiation, potentially leading to detrimental health effects. Minimal fluoroscopy (MF) represents a safer alternative, which should be explored. Data on the safety and efficacy of this technique are limited. Hypothesis Our hypothesis is that MF is of equal efficacy and safety to conventional catheter ablation with the use of fluoroscopy by performing a meta‐analysis of both randomized controlled trials (RCTs) and real‐world regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Many published articles reported the success of the ZMF approach for numerous cardiac procedures, such as catheter ablations and correction of congenital heart diseases. Arrhythmia termination using the ZMF approach (3D‐EAMS) was not inferior compared to conventional fluoroscopy 5,18,19 . Meanwhile, transcatheter correction under echocardiography guidance could also be done to treat atrial septal defect and patent ductus arteriosus 20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many published articles reported the success of the ZMF approach for numerous cardiac procedures, such as catheter ablations and correction of congenital heart diseases. Arrhythmia termination using the ZMF approach (3D‐EAMS) was not inferior compared to conventional fluoroscopy 5,18,19 . Meanwhile, transcatheter correction under echocardiography guidance could also be done to treat atrial septal defect and patent ductus arteriosus 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmia termination using the ZMF approach (3D‐EAMS) was not inferior compared to conventional fluoroscopy. 5 , 18 , 19 Meanwhile, transcatheter correction under echocardiography guidance could also be done to treat atrial septal defect and patent ductus arteriosus. 20 , 21 Interestingly, the ZMF approach had also been performed for CIEDs implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of 3‐D mapping systems has allowed surgeons to perform ablation procedures with less radiation exposure 12 . Studies have demonstrated the safety of reduced or zero‐fluoro ablation for supraventricular arrhythmia 13–15 . Among such studies, a single‐center study by Razmania et al 14 showed no lead‐related complications in 52 patients with CIEDs who underwent zero‐fluoro ablation for various types of arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…12 Studies have demonstrated the safety of reduced or zero-fluoro ablation for supraventricular arrhythmia. [13][14][15] Among such studies, a single-center study by Razmania et al 14 showed no lead-related complications in 52 patients with CIEDs who underwent zero-fluoro ablation for various types of arrhythmias. This suggested that at experienced centers, zero-fluoro ablation can be a safe option even in the presence of CIED leads.…”
Section: Discussionmentioning
confidence: 99%